TREES AND REGENERATION IN RUBBER AGROFORESTS AND OTHER FOREST-DERIVED VEGETATION IN JAMBI (SUMATRA, INDONESIA) - Tata, Hesti L.; Noordwijk, Meine van; Werger, Marinus (Secretariat of Forestry Research and Development Agency, 2008)
The rubber Â agroforests Â (RAF)Â of Indonesia provide Â a dynamic interface Â between natural Â processes Â of forest Â regeneration and Â humanâs managementÂ Â targeting Â the harvesting Â of latexÂ with Â minimum investment Â of time Â and financial Â resources. Â The composition Â and species richness Â of higher Â plantsÂ across an intensification gradient from forest to monocultures of tree crops have been investigated Â in six land use types (viz. secondary forest, RAF, rubber monoculture, oil palm plantation, cassava field and Imperata grassland) Â in Bungo, Â Jambi Â Province, Â Indonesia. Â We emphasize Â comparison of four different Â strataÂ (understory, seedling, Â sapling Â and tree) of vegetation Â between forest and RAF, Â with Â specific interest Â in plant Â dependenceÂ on ectomycorrhiza fungi. Species richness Â and species accumulation curves for seedlingÂ and sapling Â stages were similar Â between forest and RAF, Â but in the tree stratum Â (trees > 10 cm dbh) selective thinning by farmers was evident in a reduction Â of species diversity and an increase in the proportion of trees with edible parts. Very few trees dependent on ectomycorrhiza fungi were encounteredÂ in the RAF. However, the relative distribution of early and late successional species as evident from the wood density distribution showed no difference between RAF and forest.